IMPROVING THE UTILIZATION EFFICIENCY OF SURGICAL AND PROCEDURAL INSTRUMENT SETS THROUGH THE APPLICATION OF THE HIS PRO INTEROPERABILITY SOFTWARE AT LAO CAI NO.1 GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the effectiveness of implementing a surgical instrument management software integrated with the Hospital Information System (HIS) in improving instrument utilization efficiency and optimizing management processes at the Infection Control Department of Lao Cai Provincial General Hospital No.1.Subjects and methods: A quality improvement study based on the Lean Six Sigma methodology using the DMAIC cycle was conducted. Data were collected from all surgical activities during 2024–2025, including the pre-intervention period (January–August 2024), system implementation (September–December 2024), and post-intervention evaluation (2025).Results: The number of surgeries increased from 8,100 in 2024 to 9,195 in 2025 (13.5% increase). Instrument utilization efficiency improved from 78.3% to 93.4%. The average issuing time decreased from 7.0 to 3.8 minutes per set (45.7% reduction), while the demand aggregation process was fully automated.Conclusion: Implementation of a HIS-integrated surgical instrument management system significantly improved instrument utilization efficiency, reduced processing time, and minimized unnecessary instrument issuance. This approach enhances management efficiency, optimizes healthcare resources, and contributes to improved patient safety
Keywords: Surgical instrument management; Infection control; HIS; Lean Six Sigma; Healthcare digital transformation.